2004
DOI: 10.1007/s00198-004-1746-7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment strategies for proximal femur fractures in osteoporotic patients

Abstract: Fractures of the proximal end of the femur, together with vertebral fractures, are greatly exacerbated by osteoporosis and can be regarded as the most typical and most serious complications of this disease. The demand for prompt mobilisation with full loading of the affected limb, combined with a desire for the gentlest of treatments, becomes increasingly difficult to meet in ageing patients with advanced osteoporosis. The advantages of osteosynthesis in respect to these demands when operating on elderly patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(53 citation statements)
references
References 42 publications
0
48
0
5
Order By: Relevance
“…The incidence of this disorder has increased markedly in recent years owing to continuously aging populations (Bonnaire et al, 2005). Proximal femur nail antirotation (PFNA) is a new internal fixation system that was recently developed and is now applied widely in various intertrochanteric fractures.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of this disorder has increased markedly in recent years owing to continuously aging populations (Bonnaire et al, 2005). Proximal femur nail antirotation (PFNA) is a new internal fixation system that was recently developed and is now applied widely in various intertrochanteric fractures.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, little is available to avoid fixation failure following hip fracture, such as proper patient selection, optimal reduction of the fracture and proper positioning of the fixation devices. Although significant differences were demonstrated between different regions of proximal femur by using quantitative CT, the difference between DXA measurements of different regions of proximal femur is not as much as expected (4). The reason for this may be due to 2D nature of the measurement by DXA, and effect of neighboring cortical bone on x-ray absorption.…”
Section: Resultsmentioning
confidence: 72%
“…But this finding has not been validated clinically. Also a BMD range of 260-370 mg/cm 3 calcium hydroxyapatite (CaHAp) at femoral head center was described as necessary to ensure stable fixation of hip fractures (1,4).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the success small threaded endosseous implants have achieved in modern orthopedic and dental medicine, there are still cases in which they do not perform well. Biomechanical studies have shown that prevailing small endosseous implants show decreased performance when implanted into bone with low density, such as evoked by osteoporosis (Bonnaire et al, 2005;Koistinen et al, 2005;Seebeck et al, 2004). It appears evident that there is potential to enhance implant performance.…”
Section: Introductionmentioning
confidence: 99%